Analytical Techniques for The Evaluation of Lead Concentrations in Food for Human Consumption - PEREZ, KARINA ALVARADO; ESENARRO, DORIS; PAASACA, LUIS ENRIQUE CRUZ; CORDOVA, ALCIRA; USAQUI, ROCÍO PAREJA; TOLEDO, CELESTE CERVANTES; OSORIO, ROMINA GUERRERO; HUERE, MAX BASUALDO (The journal of contemporary issues in business and government, 2021)
In the present work, a review was carried out on the studies carried out in different parts of the world, on the analysis techniques used to evaluate the concentrations of lead in various products for human consumption. A review was made of 25 arbitrary scientific articles from three databases SCOPUS, Science direct and Google academic, published from 2016 to February 2021, identifying 15 countries of origin, the country with the highest number of publications was the results with the Codex quality standard.